2019
DOI: 10.1007/s13300-019-00713-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Placenta Damage in Gestational Diabetes Mellitus by Investigating TXNIP of Patient Samples and Gene Functional Research in Cell Line

Abstract: Introduction: Gestational diabetes mellitus (GDM) is a gestational complication that affects maternal and child health. The placenta provides the fetus with the necessary nutrition and oxygen and takes away the metabolic waste. Patients with GDM are diagnosed and treated merely on the basis of the blood glucose level; this approach does nothing to help evaluate the status of the placenta, which is worth noting in GDM. The purpose of this research was to clarify the relation between thioredoxin-interacting prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Known as a highly specialized organ during pregnancy, the placenta serves as the interface between maternal and fetal circulation (35). In recent years, the key role of the placenta in the occurrence and development of GDM has been reported by multiple studies (36)(37)(38). Currently, IR is the critical pathophysiological characteristic of GDM, which is also found during normal pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Known as a highly specialized organ during pregnancy, the placenta serves as the interface between maternal and fetal circulation (35). In recent years, the key role of the placenta in the occurrence and development of GDM has been reported by multiple studies (36)(37)(38). Currently, IR is the critical pathophysiological characteristic of GDM, which is also found during normal pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological oxidative stress is indeed a protective and adaptive mechanism of the body during normal pregnancies. However, excessive active oxygen can disrupt the balance between oxidation and antioxidation, cause pathological oxidative stress, and ultimately lead to tissue damage in GDM[ 6 , 19 ]. A previous study showed that placental cell biology and mitochondrial dysfunction are central to the pathophysiology of many gestational diseases, such as GDM, preeclampsia, preterm birth, and fetal growth restriction[ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of glucose flux to the fetus is controlled by the maternal-to-fetal glucose concentration gradient across the placenta ( 33 ). Hyperglycemia-induced apoptosis of non-proliferative syncytiotrophoblast cells leaves incomplete holes in the placenta, which will cause a large flux of glucose into the fetal blood circulation ( 34 ). Data have demonstrated that women with higher FPG levels at baseline had a greater risk of developing GDM at approximately 26 weeks, which coincides with the period of elevated maternal endogenous glucose production and reduced insulin sensitivity ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%